Advanced Ultrasound Techniques for Neuroimaging in Pediatric Critical Care: A Review - Colbey W. Freeman; Misun Hwang (MDPI AG, 2022)
Because of its portability, safety profile, and accessibility, ultrasound has been integral in pediatric neuroimaging. While conventional B-mode and Doppler ultrasound provide anatomic and limited flow information, new and developing advanced ultrasound techniques are facilitating real-time visualization of brain perfusion, microvascular flow, and changes in tissue stiffness in the brain. These techniques, which include contrast-enhanced ultrasound, microvascular imaging, and elastography, are providing new insights into and new methods of evaluating pathologies affecting children requiring critical care, including hypoxic-ischemic encephalopathy, stroke, and hydrocephalus. This review introduces advanced neurosonography techniques and their clinical applications in pediatric neurocritical care.